2022
DOI: 10.3390/polym14132636
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane-Based Gel Electrolyte for Application in Flexible Electrochromic Devices

Abstract: For the application in flexible electrochromic devices (ECDs) on plastic substrates, a new polyurethane-based gel electrolyte was manufactured. In this context, the curing behavior and the influence of the proportion of solvent and salt on the ion conductivity as well as the optical and mechanical properties were investigated. Furthermore, the stoichiometric ratio of the polyurethane matrix was varied to influence the ion conductivity. As an isocyanate component, the aliphatic difunctional polyisocyanate prepo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…[ 12 ] Thermal decomposition without oxygen takes place at over 250 °C in the first stage due to thermolysis of urethane linkages and in the second stage due to decomposition of the polyol component [ 9 ]. This fits well with the previous result of a thermogravimetric analysis of the subjected polyurethane-based electrolyte [ 6 ]. Sui et al reported that during prolonged temperature storage, degradation of the hard (isocyanate dominated) segment took place first at approximately 175 °C through scission of the urethane bond to form urea, alcohols and CO 2 [ 13 ].…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…[ 12 ] Thermal decomposition without oxygen takes place at over 250 °C in the first stage due to thermolysis of urethane linkages and in the second stage due to decomposition of the polyol component [ 9 ]. This fits well with the previous result of a thermogravimetric analysis of the subjected polyurethane-based electrolyte [ 6 ]. Sui et al reported that during prolonged temperature storage, degradation of the hard (isocyanate dominated) segment took place first at approximately 175 °C through scission of the urethane bond to form urea, alcohols and CO 2 [ 13 ].…”
Section: Introductionsupporting
confidence: 92%
“…It is noticeable that, despite weathering, formulation f (0.85_5_10) retains a conductivity at a significantly higher level compared to the other formulations whose values drop comparably to the order of 10 −8 S/cm. The sub-stoichiometric ratio of the polyurethane matrix of formula f (0.85_5_10) thus seems to have a strong positive effect not only on the conductivity as prepared [ 6 ] but also on the aging resistance with respect to conductivity. Interestingly, the samples weathered in the dry nitrogen atmosphere almost retain their conductivity, with a certain variation ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of solvent also contributes to the observed ionic conductivities by increasing polymer chain mobility and free volume. 33 Furthermore, the mechanism of ion transport differs between the gel polymer electrolytes and the dry polymer electrolytes. HNBR is mostly amorphous with a small degree of critallinity.…”
Section: Ionic Conductivitymentioning
confidence: 99%